PROFIL TOKOH PENDIDIK DALAM NOVEL BURLIAN KARYA TERE-LIYE - Putra, Deded Palma; Thahar, Harris Effendi; Nurizzati, Nurizzati (Jurnal Bahasa dan Sastra, 2013)
This article aims to (1) profiles that reflect the character of prominent educators educators associated with the responsibilities of the novel Burlian the work of Tere Liye, (2) profile that reflects the character of prominent educators educators associated with care for the environment in a novel Burlian the work of Tere Liye, (3) profiles that reflect the character of prominent educators educators relating to social care in the Novel Burlian the work of Tere Liye, (4) profile that reflects the character of prominent educators educators relating to honest in the Novel Burlian the work of Tere Liye. Data collected by: (1) read the novel Burlian, (2) conducted a study of the literature, this step is performed to obtain library materials referenced in discussing Burlian novel or as a guide for researchers, and (3) data on the profile inventory educators be held responsibility, environmental care, social care and honest in the novel Burlian the work of Tere Liye. The study's findings are prominent educators who reflect the character of responsibility, care for the environment, social care, and honesty. The figures reflect the four characters of such education by giving advice and taking the example of the reality of society. Keywords: novel, profiles, character education, responsibility, care for the environment, social care, honest.